Antarctic emerald rockcod have the capacity to compensate for warming when uncoupled from CO2-acidification - Miller, Nathan; Todgham, Anne (IEDA: US Antarctic Program Data Center, 2017)
This dataset includes data from the publication Davis et al - Antarctic emerald rockcod have the capacity to compensate for warming when uncoupled from CO2-acidification. Included are data on cardiorespiratory physiology, survival, metabolic rate, metabolic enzyme activity, behavior (scototaxis & activity) and seawater chemistry.